Analisis Anteseden Kinerja Usaha Mikro Kecil Menengah (UMKM) - Sita Indriyani; Nur Laila Yuliani; Anissa Hakim Purwantini (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to empirically examine the effect of Ability to Prepare Financial Statements, Educational Background, E-Commerce, and Use of Accounting Information Systems on the Performance of Micro, Small and Medium Enterprises (MSMEs). This study uses a sample of Micro, Small and Medium Enterprises in Magelang City. Based on the purposive sampling method, the number of samples that can be processed in this study is 105 respondents. The method of data analysis in this study used multiple linear regression. The results of this study indicate that the ability to prepare financial statements, educational background, and e-commerce have a positive effect on the performance of Micro, Small and Medium Enterprises (MSMEs). While the use of Accounting Information Systems has no effect the performance of Micro, Small and Medium Enterprises (MSMEs).